Corporate reputation and customer loyalty as the measures of competitive enterprise position - empirical analyses on the example of banking sector - Danuta Szwajca (Institute of Economic Research (IER), 2015)
In order to determine the competitive position of a company not only the traditional measures of market position (market share) and financial position (financial ratios) are used but also the qualitative measures concerning intangible resources. Customer satisfaction and customer loyalty are the two most commonly applied qualitative measures. Due to the growing importance of intangible resources, and of reputation in particular, the need arises to use the reputation indicator as a measure of competitive position in achieving a long-term competitive advantage and building the enterprise value. The purpose of this article is to identify the competitive position indicated by the level of corporate reputation in comparison with the customer loyalty indicator and the most popular traditional measures based on the example of banking sector. For calculation of qualitative measures the method of survey was used, conducted among the retail banking customers. The study showed a weak relationship between reputation and loyalty: the banks that received the highest ratings of reputation, obtained the poorest results in terms of loyalty. Due to the limited subjective and methodological scope of research, the results cannot constitute a sufficient basis to prove this thesis, however, they may constitute a good starting point for conducting broader research in this area.
Keywords: G21; L14; L25; M31; 330; reputation; customer loyalty; competitive position; banking sector